2019
DOI: 10.7150/ijms.35611
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Genes in Osteoarthritic Fibroblast-Like Synoviocytes Using Next-Generation Sequencing and Bioinformatics Approaches

Abstract: Synovitis in osteoarthritis (OA) the consequence of low grade inflammatory process caused by cartilage breakdown products that stimulated the production of pro-inflammatory mediators by fibroblast-like synoviocytes (FLS). FLS participate in joint homeostasis and low grade inflammation in the joint microenvironment triggers FLS transformation. In the current study, we aimed to identify differentially expressed genes and potential miRNA regulations in human OA FLS through deep sequencing and bioinformatics appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 76 publications
1
9
0
Order By: Relevance
“… Tanaka et al (2016) revealed that SKAP2 is related to tumor-associated macrophage infiltration and facilitates the metastatic progression of lung cancer in mise. The prognostic value of SKAP2 was also reported in previous studies using bioinformatics analyses ( Kuranami et al, 2015 ; Tanaka et al, 2016 ; Chen et al, 2019 ). Studies showed that CDH4 could be regulated by miR-211-5p to inhibit the proliferation, migration, and invasion of LUAD ( Zhang et al, 2020 ).…”
Section: Discussionsupporting
confidence: 72%
“… Tanaka et al (2016) revealed that SKAP2 is related to tumor-associated macrophage infiltration and facilitates the metastatic progression of lung cancer in mise. The prognostic value of SKAP2 was also reported in previous studies using bioinformatics analyses ( Kuranami et al, 2015 ; Tanaka et al, 2016 ; Chen et al, 2019 ). Studies showed that CDH4 could be regulated by miR-211-5p to inhibit the proliferation, migration, and invasion of LUAD ( Zhang et al, 2020 ).…”
Section: Discussionsupporting
confidence: 72%
“…Arthritic joints are characterized by rearrangements and dysregulated gene expression of bone, cartilage and synovial tissues [88,89]. The exact molecular and cellular events leading to the development of the different kinds of arthritis still remain elusive, but involvement of HOX gene regulation in the key tissues affected by rheumatic muscular-skeletal diseases indicate a potential link between arthritis development and HOX transcription factors.…”
Section: Hox Genes In Joint and Bone Diseasementioning
confidence: 99%
“…Considering FLS as essential participants in joint homeostasis and contributors to OA synovial pathology, it is not surprising that OA FLS show differential miRNA profiles. Recently, deep sequencing identified 245 differentially expressed genes in OA FLS and bioinformatics analyses highlighted “ECM organization and altered cellular movement” as one of the most enriched OA FLS functions connected to the differentially expressed genes and miRNA network ( 21 ). OA FLS also exhibit an independent miRNA signature from rheumatoid arthritis (RA) FLS, negatively correlating to the expression levels of their putative target genes ( 22 ).…”
Section: Mirnas In Oa Synovial Pathologymentioning
confidence: 99%
“…Integrated analyses examining miRNA and transcript profiles in parallel will help elucidate dysregulated miRNA and RNA interactions occurring in OA. In OA, Chen et al performed RNA sequencing alongside small RNA sequencing in OA FLS compared to those derived from healthy tissue ( 21 ). Putative targets of dysregulated miRNAs were predicted by bioinformatic approaches, including 14 genes (11 upregulated and 3 downregulated) that require further biological validations ( 21 ).…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation